2017
DOI: 10.1186/s13059-016-1142-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrated genome-wide analysis of expression quantitative trait loci aids interpretation of genomic association studies

Abstract: BackgroundIdentification of single nucleotide polymorphisms (SNPs) associated with gene expression levels, known as expression quantitative trait loci (eQTLs), may improve understanding of the functional role of phenotype-associated SNPs in genome-wide association studies (GWAS). The small sample sizes of some previous eQTL studies have limited their statistical power. We conducted an eQTL investigation of microarray-based gene and exon expression levels in whole blood in a cohort of 5257 individuals, exceedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
178
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 166 publications
(186 citation statements)
references
References 60 publications
(139 reference statements)
7
178
0
1
Order By: Relevance
“…In total, we related genotypes for 39,165 genome-wide significant GWAS SNPs reported to be associated with 1,960 traits in GWAS databases with expression levels of 17,873 genes to identify cis-and trans-eQTLs and their associated eGenes. 17 Our results reveal that a large number of eQTLs regulate gene expression in both a cis and trans manner. Additionally, we identified 13 trans-eQTL hotspots and found that about one third of trans regulation is significantly mediated by the expression of cis-eGenes.…”
Section: Introductionmentioning
confidence: 73%
“…In total, we related genotypes for 39,165 genome-wide significant GWAS SNPs reported to be associated with 1,960 traits in GWAS databases with expression levels of 17,873 genes to identify cis-and trans-eQTLs and their associated eGenes. 17 Our results reveal that a large number of eQTLs regulate gene expression in both a cis and trans manner. Additionally, we identified 13 trans-eQTL hotspots and found that about one third of trans regulation is significantly mediated by the expression of cis-eGenes.…”
Section: Introductionmentioning
confidence: 73%
“…17 Our results reveal that a large number of eQTLs regulate gene expression in both a cis and trans manner. Additionally, we identified 13 trans-eQTL hotspots and found that about one third of trans regulation is significantly mediated by the expression of cis-eGenes.…”
Section: Introductionmentioning
confidence: 93%
“…We interrogated publicly available expression quantitative trait loci (eQTL) datasets through GTEx, ENCODE, RoadMap projects, PhenoScanner 27 , STARNET 25 and Framingham Heart Study 26 to further highlight potential causal genes and mechanisms at each of the newly identified BP loci (Supplemental Table 3). The PP-associated SNV, rs13303, at STAB1 is correlated (r 2 > 0.8 1000G EUR) with the top eQTLs for NT5DC2 in atherosclerotic-lesion free internal mammary artery, atherosclerotic aortic root, subcutaneous adipose, visceral abdominal fat and liver tissues (all P < 1×10 −11 ) 25 .…”
Section: Resultsmentioning
confidence: 99%
“…24 and STARNET 25 . In addition we used the FHS eQTL results from microarray-based gene and exon expression levels in whole blood from 5,257 individuals 26 . We queried whether any of the five BP-associated SNVs were eQTLs for genes in the five BP-associated regions, or whether they were in LD (r 2 > 0.8) with any of the eQTLs for genes in these regions.…”
Section: Methodsmentioning
confidence: 99%